(untitled) (Biological Sciences - PJSIR, 2021)
Different solvent extracted samples obtained from the leaves and fruits of Melia azedarach were investigated for their antibacterial and antifungal activities. All the extracts from both tissues sources showed varying degrees of antimicrobial activities. Ethyl acetate and n-butanol extracts of both tissues inhibited the growth of the tested micro-organisms at all concentrations. N-hexane extracted fractions of the leaves reduced the activity of Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa at all concentrations, while no growth inhibition was recorded against Klebsiella pneumonia and Candida albicans. Crude methanolic extract from the leaves tissues showed activity against all the tested microbial species and highest susceptibility was noted against Bacillus subtilis. In case of leaves, the most susceptible bacteria were Bacillus subtilis (gram positive) and Klebsiella pneumonia (gram negative) was the most resistant one. In case of fruits extracts, the most susceptible bacteria were Klebsiella pneumonia (gram negative) and Escherichia coli (gram negative) was the most resistant one.